Keratopigmentation to Change the Apparent Color of the Human Eye: A Novel Indication for Corneal Tattooing. Issue 4 (April 2016) - Alió, Jorge L.; Rodriguez, Alejandra E.; El Bahrawy, Mohamed; Angelov, Alexander; Zein, Ghasam
Abstract : Background: Recently developed surgical techniques of keratopigmentation, assisted by femtosecond laser technology, using adequately developed micronized mineral pigments, have been reported to be efficient and conveniently safe as they are not associated with significant sight-threatening complications for changing the apparent color of the eye in cases of cosmetic therapeutic and functional keratopigmentation. We report the use of intrastromal keratopigmentation for electively changing the apparent color of the eyes, for purely cosmetic reasons. Methods: In a case series, 7 patients underwent purely cosmetic keratopigmentation to change the apparent color of the eye. The indication was compassionate and the procedure was conducted under the tenets of the Helsinki Declaration. Superficial automated keratopigmentation, manual intralamellar keratopigmentation, and femtosecond-assisted keratopigmentation were used. In this study cosmetic outcome, patient satisfaction, visual outcomes, stability of pigmentation, and presence of any related complications are reported. Results: In this study 42.8% were females, with a mean age of 40 years (27–63). In 4 patients, pigment retouch was done to improve the cosmetic outcome. Results were monitored by an independent observer with follow-up ranging from 6 months to 2.5 years. All patients expressed high satisfaction with the cosmetic outcomes, with no complications and stable visual acuity during the period of follow-up. Conclusions: As a novel indication, purely cosmetic keratopigmentation demonstrated stable pigmentation with no visual disability, high patient satisfaction, and favorable outcomes in all patients. Elective keratopigmentation seems to be a viable and convenient modality for changing the apparent color of the eye in selected cases.